2016
DOI: 10.1177/1591019916669090
|View full text |Cite
|
Sign up to set email alerts
|

Prasugrel versus clopidogrel in stent-assisted coil embolization of unruptured intracranial aneurysms

Abstract: Background Thromboembolic complications are the main problem in stent-assisted coil embolization of unruptured intracranial aneurysms. The combination of aspirin and clopidogrel is generally used to decrease these complications, but some patients do not respond to clopidogrel and have a higher risk of stent thrombosis. In cardiology, clinical trials have shown that prasugrel reduced the incidence of ischaemic events in patients with acute coronary syndrome compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 46 publications
(102 reference statements)
1
28
0
Order By: Relevance
“…Sedat et al compared two cohorts, one treated with aspirin plus clopidogrel, and the other with aspirin plus prasugrel. Although the number of thromboembolic events did not differ statistically, clopidogrel appeared to be associated with three times more serious statistically significant thromboembolic events, such as complete stent thrombosis at 30 days30. Overall, our complication rate compares favourably with rates reported in the literature, with meta-analysis compiling total complication rates of 10.9–17.6%, with a 6.8–9.1% mortality rate, thromboembolic complication rate of 4.2%, and permanent complication rate of 3.8–5.6% recorded8.…”
Section: Discussionmentioning
confidence: 66%
“…Sedat et al compared two cohorts, one treated with aspirin plus clopidogrel, and the other with aspirin plus prasugrel. Although the number of thromboembolic events did not differ statistically, clopidogrel appeared to be associated with three times more serious statistically significant thromboembolic events, such as complete stent thrombosis at 30 days30. Overall, our complication rate compares favourably with rates reported in the literature, with meta-analysis compiling total complication rates of 10.9–17.6%, with a 6.8–9.1% mortality rate, thromboembolic complication rate of 4.2%, and permanent complication rate of 3.8–5.6% recorded8.…”
Section: Discussionmentioning
confidence: 66%
“…Neither of these studies ( n = 136) adjusted the antiplatelet regime in the setting of proven clopidogrel resistance. Sedat et al [24] found similar rates of thromboembolic events when either clopidogrel or prasugrel was used. A study from Brinjikji et al [12] assessed neurologic morbidity and mortality in patients with and without PFT for clopidogrel resistance in NVS procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies reported outcomes of patients undergoing neuroendovascular procedures managed on clopidogrel therapy compared with prasugrel therapy. 16,[22][23][24][25][26][27] Overall, prasugrel therapy in clopidogrel hyporesponders was associated with a similar rate of thrombotic complications compared with clopidogrel use in responders, with two of the seven comparative studies reporting a statistically significant decrease in thromboembolic complications. 26,27 Prasugrel also appeared to have similar rates of hemorrhagic complications, although one study 22 reported a higher rate of hemorrhagic complications compared with clopidogrel (19.4% vs 3.6%, p=0.02) in a heterogeneous population undergoing neuroendovascular procedures including stentassisted coiling (34.9%), aneurysm coiling (25.6%), PED placement (18.6%), extra-or intracranial carotid angioplasty and stenting (12.8%), onyx embolization (7%), and dural arteriovenous fistula coil embolization (1.2%).…”
Section: Prasugrelmentioning
confidence: 95%
“…Loading doses ranged from 20–60 mg, and maintenance doses ranged from 5–10 mg/day. Seven studies reported outcomes of patients undergoing neuroendovascular procedures managed on clopidogrel therapy compared with prasugrel therapy . Overall, prasugrel therapy in clopidogrel hyporesponders was associated with a similar rate of thrombotic complications compared with clopidogrel use in responders, with two of the seven comparative studies reporting a statistically significant decrease in thromboembolic complications .…”
Section: Options For Periprocedural Antiplatelet Therapymentioning
confidence: 99%